A metal electrode for aluminum electrolysis and its coating composition and preparation method
By applying a coating composition composed of NiFe2O4 and metal components on the surface of the aluminum electrolytic inert anode, the problems of short service life and corrosion of the anode are solved, and the effects of prolonging electrolysis time and stabilizing impurity content are achieved.
Patent Information
- Application Number
- CN202310376813.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing aluminum electrolytic inert anode has a short service life, and it is easy to form an oxide layer during the electrolysis process to cause corrosion, affecting the electrolytic efficiency and the purity of the aluminum liquid.
A coating composition using a metal electrode for aluminum electrolysis, the components include NiFe2O4: 65%-75% and metal components: 25%-35%, wherein the metal components include Ni, Fe and Y, and the coating composition is It is granular, with a volume particle size of 55-70 μm and a coating thickness of 250-350 μm. It is applied to the surface of the NiFe metal anode through a plasma spraying process.
Effectively reduce the erosion of high-temperature electrolytic molten salt on the metal anode matrix, maintain the stability of the film layer thickness, extend the service life of the metal anode to 35-45 weeks, stabilize the electrolytic primary aluminum metal impurity content below 0.7%, solving the short electrolytic time and The problem of poor stability of impurity content.
Smart Images

Figure CN117004256B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum electrolysis, and in particular to a metal electrode for aluminum electrolysis, a coating composition thereof, and a preparation method thereof. Background Art
[0002] Inert anode aluminum electrolysis technology does not consume carbon anodes and does not emit CO2. What is emitted during the electrolysis process is O2. There is no need to change the anode, which greatly reduces the labor intensity of workers, improves the working environment of workers, saves a lot of carbon resources, is environmentally friendly, and conforms to the concept of green development. Green aluminum electrolysis technology with inert anode as the core is an important strategic support for the upgrading of the aluminum industry.
[0003] At present, the selection of inert anode materials is mainly concentrated in three aspects: metal alloy anode, oxide ceramic anode and metal ceramic anode. The article "Research Status of Inert Anode for Aluminum Electrolysis" points out that metal inert anode has excellent conductivity and mechanical properties, is suitable for processing and forming and preparing complex shape spare parts, is easy to connect with metal guide rods, and has easy access to raw materials and low processing costs. It has become one of the most promising inert anode materials and has received much attention from various research institutions and enterprises. However, alloy anodes have a fatal disadvantage: poor corrosion resistance to high-temperature molten salts. During the electrolysis of metal anodes, a dense oxide layer will form on the surface of the anode, otherwise the metal anode will be directly corroded by the electrolyte. When the anode is polarized and not passivated, this corrosion will intensify and lead to direct electrostripping of the anode metal, resulting in the disastrous result of abnormal interruption of electrolysis.
[0004] The metal on the working surface of the metal anode is very easy to undergo oxidation reaction with the newly generated oxygen in the electrolytic reaction. The oxide and alloy matrix dissolve into the electrolyte, diffuse to the cathode aluminum liquid, and then are reduced into the aluminum liquid, which not only shortens the service life of the metal anode, but also causes problems such as high pollution of the newly generated aluminum. Therefore, the research on alloy anodes mainly focuses on how to reduce the corrosion rate of alloys and extend the service life of anodes. To this end, the research on alloy anodes is mainly carried out through the following two ways: one is to optimize the alloy anode material system and microstructure, add alloy elements, and improve the corrosion resistance of the alloy in the cryolite high-temperature molten salt system. The second is to form a dense and corrosion-resistant oxide film or coating on the surface of the alloy anode in advance through surface modification technologies such as pre-oxidation, surface spraying, and chemical deposition to avoid direct contact between the metal matrix and the electrolyte, thereby protecting the alloy matrix. Summary of the invention
[0005] The present application provides a metal electrode for aluminum electrolysis and a coating composition and a preparation method thereof, so as to improve the problem of short service life of the metal anode.
[0006] In a first aspect, the present application provides a coating composition for a metal electrode for aluminum electrolysis, wherein the components of the coating composition include, by mass fraction: NiFe2O4: 65%-75% and metal component: 25%-35%; wherein the chemical composition of the metal component includes: Ni, Fe and Y.
[0007] As an optional embodiment, the chemical composition of the metal component includes, by mass fraction: Ni: 55%-65%, Fe: 35%-45% and Y: 0.5%-1.5%.
[0008] As an optional embodiment, the coating composition is in granular form;
[0009] Optionally, the volume particle size of the coating composition is 55-70 μm.
[0010] In a second aspect, the present application provides a metal electrode for aluminum electrolysis, the metal electrode comprising a substrate and a coating attached to the substrate, the coating comprising the coating composition described in the first aspect.
[0011] As an optional embodiment, the thickness of the coating is 250-350 μm; and / or
[0012] The substrate is a NiFe metal anode.
[0013] In a third aspect, the present application provides a method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0014] Obtain NiFe2O4 powder;
[0015] obtaining metal component powder;
[0016] Mixing the NiFe2O4 powder and the metal component powder to obtain a coating composition;
[0017] The coating composition is applied to the surface of a substrate to obtain a metal electrode for aluminum electrolysis.
[0018] As an optional embodiment, the obtaining of NiFe2O4 powder comprises:
[0019] Mix NiO and Fe2O3, and then calcine them to obtain NiFe2O4 powder;
[0020] Optionally, the molar ratio of NiO to Fe2O3 is 1:1;
[0021] Optionally, the calcination temperature is 900-1050°C;
[0022] Optionally, the calcination atmosphere is an air atmosphere.
[0023] As an optional embodiment, the obtaining of the metal component powder comprises:
[0024] Ni, Fe and Fe-Y master alloy are smelted and then granulated to obtain metal component powder;
[0025] Optionally, the granulation is carried out by vacuum atomization;
[0026] Optionally, the volume particle size of the metal component powder is 44-60 μm.
[0027] As an optional embodiment, the NiFe2O4 powder and the metal component powder are mixed to obtain a coating composition comprising:
[0028] The NiFe2O4 powder and the metal component powder are dispersed in a solvent, and then spray granulated to obtain a coating composition;
[0029] Optionally, the solvent is deionized water;
[0030] Optionally, the volume particle size of the coating composition is 55-70 μm;
[0031] Optionally, the process parameters of the spray granulation include: a processing capacity of 45-55 kg / h, an atomization pressure of 3-5 MPa, and a discharge temperature of 85-95°C.
[0032] As an optional implementation, the coating method is spraying;
[0033] Optionally, the spraying adopts a plasma spraying process;
[0034] Optionally, the process parameters of the plasma spraying process include: a powder feeding gas flow rate of 0.5-0.6m 3 / h, the moving speed of the spray gun is 900-1000mm / min, and the spraying distance is 80-100mm.
[0035] Optionally, the coating has a coating thickness of 250-350 μm.
[0036] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0037] The coating composition provided in the embodiment of the present application can be applied to the surface of the existing corrosion-resistant NiFe-based metal anode, which can not only effectively reduce the direct erosion of the high-temperature electrolytic molten salt on the metal anode substrate, but also can dissolve the protective coating surface while regenerating a protective film layer from the substrate and the plating layer, thereby achieving a dynamic relative balance between corrosion oxidation and dissolution of the metal anode, maintaining the relative stability of the film thickness during its service life, greatly delaying the consumption of the metal anode, and increasing its service life from the existing several hours to dozens of hours to 35-45 weeks. The impurity content of the electrolytic raw aluminum can also be stably below 0.7% for a long time, overcoming the problems of the prior art of short electrolysis time and even shorter stabilization time of the low content of impurities in the electrolytic raw aluminum. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0040] Figure 1 The surface morphology of the uncoated metal anode provided in the embodiment of the present application;
[0041] Figure 2 A surface morphology of a metal anode with a coating provided in an embodiment of the present application;
[0042] Figure 3 A cross-sectional SEM image of the coating of the metal electrode provided in the embodiment of the present application;
[0043] Figure 4 This is a SEM image of the metal electrode after electrolysis provided in the embodiment of the present application;
[0044] Figure 5 A flowchart of a method provided in an embodiment of the present application.
[0045] Figure numerals: 1- oxide layer, 2- substrate, 3- interpenetration zone between surface layer and substrate, 4- coating. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0047] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0048] like Figure 1 As shown, an embodiment of the present application provides a coating composition for a metal electrode for aluminum electrolysis, wherein the components of the coating composition include, by mass fraction: NiFe2O4: 65%-75% and metal component: 25%-35%; wherein the chemical composition of the metal component includes: Ni, Fe and Y.
[0049] In some embodiments, the chemical composition of the metal component includes, by mass fraction, Ni: 55%-65%, Fe: 35%-45%, and Y: 0.5%-1.5%.
[0050] The metal on the working surface of the alloy anode is very easy to react with the newly generated oxygen in the electrolytic reaction. The oxide and the alloy matrix dissolve into the electrolyte, diffuse to the cathode aluminum liquid, and then are reduced and enter the aluminum liquid, causing high pollution of the newly generated aluminum. This coating is to avoid direct contact between the metal matrix and the high-temperature molten salt, and to protect the matrix metal anode. The service environment of the electrolytic anode requires that the coating must have good conductivity, thermal stability, oxidation resistance and corrosion resistance. NiFe2O4 ceramic phase has good conductivity, thermal stability, strong corrosion resistance and strong high-temperature oxidation resistance to the electrolyte. Therefore, the coating component selects NiFe2O4 as the basic raw material for preparing the coating, and controls the NiFe2O4 ceramic phase content at 65%-75%, and the balance is the metal phase, which can not only play the due protective role, but also further improve the conductivity of the coating. If the mass fraction of the NiFe2O4 ceramic phase is too large, not only its thermal vibration will deteriorate, but also its conductivity will decrease, increasing reactive power consumption. If it is too small, the protective performance will be insufficient, affecting the service life of the inert electrode.
[0051] The introduction of metal components can improve the thermal shock resistance of NiFe2O4 ceramic phase, and its main function is to improve the conductivity of the coating. The coating reacts with the newly generated oxygen of electrolytic alumina in the electrolytic environment to produce nickel and iron oxides, reduce their corrosion diffusion rate, and further improve the protective performance of the coating. The mass fraction of the metal component is controlled at 25%-35%. If it is too high, it will increase the corrosion rate and shorten the protective period of the coating. If it is too low, the improvement of conductivity will be limited. Among them, nickel and iron can form new oxides with the newly generated oxygen of electrolytic alumina on the surface of the coating in the electrolytic environment, which plays a protective role and reduces the corrosion diffusion rate of the coating. Controlling the two in a specific mass fraction range, its role is to form an oxygen-containing atmosphere microenvironment in the high-temperature electrolytic environment. The two oxides can be partially generated as NiFe2O4 ceramic phases, further improving the corrosion resistance of the coating. The added rare earth element Y is mainly enriched in the phase boundary and grain boundary. The large atomic rare earth in the interface blocks the diffusion channel of metal elements such as Fe and Ni, and also blocks the diffusion of atoms such as oxygen and fluorine in the electrolytic environment, effectively inhibiting the corrosion diffusion rate of metal elements and improving the service life of the coating. In addition, due to the strong affinity of rare earth elements with oxygen and the unique "pinning effect" of rare earth elements, the oxidation resistance of the alloy and the bonding strength between the film layer and the substrate can be improved, and an oxidation-resistant film layer that is more resistant to electrolyte melt corrosion can be generated. The rare earth Y content of this coating is controlled within the range of 0.5%-1.5%. If it is too low, the effect is not obvious, and if it is too high, the preparation cost will increase, which is not conducive to industrial-scale application.
[0052] In some embodiments, the coating composition is in a granular form; optionally, the volume particle size of the coating composition is 55-70 μm.
[0053] The volume particle size of the coating composition is controlled at 55-70μm. The spraying quality is good within this particle size range, the powder has good fluidity, is easy to disperse, and the spraying temperature is appropriate. If the particle size is too large, the spraying temperature will increase, the bonding strength between the spray layer and the substrate will deteriorate, and the surface smoothness will decrease. If the particle size is too small, the powder has poor fluidity, is easy to agglomerate, and is easy to clog the nozzle during the spraying process.
[0054] Based on a general inventive concept, an embodiment of the present application further provides a metal electrode for aluminum electrolysis, the metal electrode comprising a substrate and a coating attached to the substrate, the coating comprising the coating composition provided above.
[0055] In some embodiments, the coating has a thickness of 250-350 μm, and the substrate is a NiFe metal anode.
[0056] The reason for controlling the coating thickness to 250-350μm is to ensure that the protection period of the metal inert anode is prolonged as much as possible without adversely affecting the bonding strength between the coating and the substrate. The adverse effect of too large a thickness is that the bonding strength between the coating and the substrate becomes lower, and in severe cases, cracks or even falling off may occur. The adverse effect of too small a thickness is that the protective effect is reduced and the service life of the inert metal anode is shortened.
[0057] Plasma spraying of an anti-oxidation and corrosion-resistant layer on the surface of the existing corrosion-resistant NiFe-based metal anode can not only effectively reduce the direct erosion of the high-temperature electrolytic molten salt on the metal anode substrate, but also can regenerate a protective film layer from the substrate and the coating while the protective coating surface is dissolved, thereby achieving a dynamic relative balance between corrosion oxidation and dissolution of the metal anode, maintaining the relative stability of the film thickness during its service life, greatly delaying the consumption of the metal anode, and increasing its service life from the existing several hours to dozens of hours to 35-45 weeks. The content of metallic impurities in electrolytic raw aluminum can also be stably lower than 0.7% for a long time, overcoming the problems of short electrolysis time and shorter stability time of low content of metallic impurities in electrolytic raw aluminum in the prior art. Moreover, in the process of using the metal anode of the present invention, as the electrolysis process is improved, the service life of the inert anode will be further extended, thereby realizing the universal application of the inert anode in industrial electrolytic production.
[0058] like Figure 5 As shown, based on a general inventive concept, the present application embodiment also provides a method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0059] S1. Obtain NiFe2O4 powder;
[0060] In some embodiments, obtaining NiFe2O4 powder includes: mixing NiO and Fe2O3, and then calcining to obtain NiFe2O4 powder.
[0061] Specifically, in this embodiment, NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneader, and then calcined at 900-1050° C. in an air atmosphere to form NiFe2O4 ceramic powder.
[0062] S2. Obtaining metal component powder;
[0063] In some embodiments, obtaining the metal component powder includes: smelting Ni, Fe and Fe-Y master alloy, and then granulating to obtain the metal component powder.
[0064] Specifically, in this embodiment, Ni, Fe and Fe-Y master alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization.
[0065] S3. The NiFe2O4 powder and the metal component powder are mixed to obtain a coating composition;
[0066] In some embodiments, the mixing of the NiFe2O4 powder and the metal component powder to obtain a coating composition includes: dispersing the NiFe2O4 powder and the metal component powder in a solvent, and then spraying and granulating to obtain a coating composition.
[0067] Specifically, in this embodiment, the calcined NiFe2O4 ceramic powder and the metal powder are mixed in proportion, deionized water is added and stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm. Further, the process parameters of the spray granulation include: a processing capacity of 45-55 kg / h, an atomization pressure of 3-5 MPa, and a discharge temperature of 85-95 ° C.
[0068] S4. Apply the coating composition to the surface of the substrate to obtain a metal electrode for aluminum electrolysis.
[0069] In some embodiments, the coating is performed by spraying.
[0070] Specifically, in this embodiment, the mixed powder is uniformly sprayed onto the surface of the NiFe metal anode using a plasma spraying process, and the thickness thereof is 250-350 μm. Further, the process parameters of the plasma spraying process include: the powder feeding gas flow rate is 0.5-0.6 m 3 / h, the moving speed of the spray gun is 900-1000mm / min, and the spraying distance is 80-100mm.
[0071] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0072] Example 1
[0073] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0074] NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneading machine, and then pre-sintered at 900-1050° C. in an air atmosphere to synthesize NiFe2O4 ceramic powder, Ni, Fe, and Fe-Y intermediate alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization method, NiFe2O4 powder and metal powder are mixed in a mass ratio of 75%:25%, deionized water is added and fully stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm, and the mixed powder is uniformly sprayed onto the surface of a Ni-Fe-based metal anode with a size of 180*150*30 mm by a plasma spraying process, with a spraying thickness of 250 μm, as a stand-by electrolytic anode.
[0075] Example 2
[0076] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0077] NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneading machine, and then pre-sintered at 900-1050° C. in an air atmosphere to synthesize NiFe2O4 ceramic powder, Ni, Fe, and Fe-Y intermediate alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization, NiFe2O4 powder and metal powder are mixed in a ratio of 72%:28%, deionized water is added and fully stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm, and the mixed powder is uniformly sprayed onto the surface of a Ni-Fe-based metal anode with a size of 180*150*30 mm by a plasma spraying process, with a spraying thickness of 280 μm, as a stand-by electrolytic anode.
[0078] Example 3
[0079] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0080] NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneading machine, and then pre-sintered at 900-1050° C. in an air atmosphere to synthesize NiFe2O4 ceramic powder, Ni, Fe, and Fe-Y intermediate alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization, NiFe2O4 powder and metal powder are mixed in a ratio of 70%:30%, deionized water is added and fully stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm, and the mixed powder is uniformly sprayed onto the surface of a Ni-Fe-based metal anode with a size of 180*150*30 mm by a plasma spraying process, with a spraying thickness of 300 μm, as a stand-by electrolytic anode.
[0081] Example 4
[0082] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0083] NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneading machine, and then pre-sintered at 900-1050° C. in an air atmosphere to synthesize NiFe2O4 ceramic powder, Ni, Fe, and Fe-Y intermediate alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization, NiFe2O4 powder and metal powder are mixed in a ratio of 68%:32%, deionized water is added and fully stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm, and the mixed powder is uniformly sprayed onto the surface of a Ni-Fe-based metal anode with a size of 180*150*30 mm by a plasma spraying process, with a spraying thickness of 330 μm, as a stand-by electrolytic anode.
[0084] Example 5
[0085] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0086] NiO and Fe2O3 with a molar ratio of 1:1 are uniformly stirred by a kneading machine, and then pre-sintered at 900-1050° C. in an air atmosphere to synthesize NiFe2O4 ceramic powder, Ni, Fe, and Fe-Y intermediate alloy are vacuum smelted to prepare Ni-Fe-Y ternary master alloy, and metal powder with a particle size of 44-60 μm is obtained by vacuum atomization, NiFe2O4 powder and metal powder are mixed in a ratio of 65%:35%, deionized water is added and fully stirred by a stirring mill, granulated by a spray granulator, and then sieved to obtain a mixed powder with a particle size of 55-70 μm, and the mixed powder is uniformly sprayed onto the surface of a Ni-Fe-based metal anode with a size of 180*150*30 mm by a plasma spraying process, with a spraying thickness of 350 μm, as a stand-by electrolytic anode.
[0087] Comparative Example 1
[0088] A nickel-iron based metal with a size of 180*150*30 mm is used as the electrolysis anode.
[0089] Comparative Example 2
[0090] A method for preparing a metal electrode for aluminum electrolysis, the method comprising:
[0091] A nickel-iron-based metal anode with a size of 180*150*30mm is placed in a heat treatment furnace for pre-oxidation treatment at 1000°C for 10 hours. After a protective layer with a thickness of about 100μm is formed on the surface of the nickel-iron-based metal anode, it is used as an electrolytic anode.
[0092] The metal electrodes provided in Examples 1 to 5 and Comparative Examples 1 to 2 were used as anodes to assemble an electrolysis device for performance testing. The specific process is as follows: Hot isostatically pressed TiB2 was used as the cathode, the cathode and anode were vertically structured, and the electrolysis current density was 0.5 A / cm 2 The electrolysis test uses a KF-NaF-AlF3 electrolyte system, with a KF content of about 20wt%, a molecular ratio of 1.4-1.5 (the sum of the moles of sodium fluoride and potassium fluoride divided by the moles of aluminum fluoride ([NaF]+[KF]) / [AlF3]), an alumina content of 4.2wt%-5.2wt%, and a temperature of 820°C. The test results are shown in the following table:
[0093]
[0094]
[0095] It can be seen from the above table that the service life of the metal electrode prepared by the method provided in the embodiment of the present application is increased from the existing several hours to dozens of hours to 35-45 weeks, and the impurity content of the electrolytic raw aluminum can also be stably lower than 0.7% for a long time.
[0096] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0097] In this application, unless otherwise specified, directional words such as "upper" and "lower" used refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the terms "include", "comprise", etc. mean "including but not limited to".
[0098] In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively.
[0099] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A metal electrode for aluminum electrolysis, characterized in that: The metal electrode comprises a substrate and a coating layer attached to the substrate, wherein the components of the coating layer are, by mass fraction, NiFe2O4: 65%-75% and metal component: 25%-35%, the chemical components of the metal component are, by mass fraction, Ni: 55%-65%, Fe: 35%-45% and Y: 0.5%-1.5%, the coating composition is in granular form, the volume particle size of the coating composition is 55-70 μm, the thickness of the coating layer is 250-350 μm, and the substrate is a NiFe metal anode.
2. A method for preparing a metal electrode for aluminum electrolysis as claimed in claim 1, characterized in that: The method comprises: Obtain NiFe2O4 powder; obtaining metal component powder; Mixing the NiFe2O4 powder and the metal component powder to obtain a coating composition; The coating composition is applied to the surface of a substrate to obtain a metal electrode for aluminum electrolysis.
3. The method for preparing a metal electrode for aluminum electrolysis according to claim 2, characterized in that: The NiFe2O4 powder is obtained by: Mix NiO and Fe2O3, and then calcine them to obtain NiFe2O4 powder; The molar ratio of NiO to Fe2O3 is 1:1; The calcination temperature is 900-1050°C; The calcination atmosphere is air atmosphere.
4. The method for preparing a metal electrode for aluminum electrolysis according to claim 2, characterized in that: The obtaining of the metal component powder comprises: Ni, Fe and Fe-Y master alloy are smelted and then granulated to obtain metal component powder; The granulation is carried out by vacuum atomization.
5. The method for preparing a metal electrode for aluminum electrolysis according to claim 2, characterized in that: The NiFe2O4 powder and the metal component powder are mixed to obtain a coating composition, comprising: The NiFe2O4 powder and the metal component powder are dispersed in a solvent, and then spray granulated to obtain a coating composition; The solvent is deionized water; The process parameters of the spray granulation include: a processing capacity of 45-55 kg / h, an atomization pressure of 3-5 MPa, and a discharge temperature of 85-95°C.
6. The method for preparing a metal electrode for aluminum electrolysis according to claim 2, characterized in that: The coating method is spraying; The spraying adopts a plasma spraying process; The process parameters of the plasma spraying process include: the powder feeding gas flow rate is 0.5-0.6m 3 / h, the moving speed of the spray gun is 900-1000mm / min, and the spraying distance is 80-100mm.
Citation Information
Patent Citations
Surface treatment method for aluminum electrolyzing inert anode
CN103820816A
Preparation process for ceramic oxidation film resistant to fused salt corrosion
CN105420659A